Theory of Social Representations: history, processes and approaches (Research, Society and Development, 2020)
This article aims to present the Theory of Social Representations (RS) as a methodological and didactic reference for research that has the human being and his social relations as his object of study or focus. To this end, we will initially present a brief epistemological framework, with contributions from authors who were instrumental in the development of the theory. Then, it seeks to conceptualize Social Representation, deepening the processes and approaches presented by other authors from Serge Moscovici. For the present research, a bibliographic study was made with materials published by classic and contemporary authors about the theory in question. Since Social Representation is a translation of reality, which is constantly changing, dynamic and mobile, with the initial idea that there are different ways to communicate and get to know each other, the study carried out showed that the Theory of Social Representations is a important approach to studies aimed at a deeper understanding and explanation of social phenomena.